Development of a Low Cost Assistive Listening System for Hearing-Impaired Student Classroom - Setha Pan-ngum; Tharapong Soonrach; Sangvorn Seesutas; Anukool Noymai; Pasin Israsena (The Scientific World Journal)
This paper describes the design, development, and tests of a low cost ALS. It was designed for hearing-impaired student classrooms. It utilised digital wireless technology and was aimed to be an alternative to a popular FM ALS. Key specifications include transmitting in 2.4 GHz ISM band with eight selectable transmission channels, battery operated and chargeable, pocket size, and ranged up to thirty metres. Audio characteristics and user tests show that it is comparable to a commercial system, currently employed in our partner school. The results also show that wearing an ALS clearly improves hearing of hearing-impaired students. Long-term usage by school children will be monitored to evaluate the system robustness and durability.